Civitas dei, civitas diaboli. Temas y topoi en la literatura española - Vasas, László (Acta Hispanica, 2014)
The present article analyses some of the features that characterize the city as theme, especially regarding its expression in Spanish literature. First of all, it focuses on the relations between this theme and textuality, relevant objectives of its configuration, properties along with literary proceedings. Next, it deals with the main topics of description, laudation and vituperation. Finally, two fragments appearing out of its plot context of the medieval Libro de Alexandre and the baroque El burlador de Sevilla are presented with an attempt of their justification and interpretation.